2014
DOI: 10.1159/000360304
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Dexamethasone Implant in Patients with Persistent Macular Edema of Variable Etiologies

Abstract: Purpose: To examine the effect of an intravitreal dexamethasone drug delivery system (DEX-DDS) in the treatment of persistent cystoid macular edema (CME) of different etiologies. Methods: Thirty-seven eyes with persistent CME were treated with DEX-DDS and analyzed for changes in best-corrected visual acuity (BCVA) and optical coherence tomography. Eyes were categorized into three groups: diabetic macular edema (DME, n = 14), vein occlusion (n = 15) and uveitis (n = 7). Results: The mean follow-up was 22 ± 6.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…Two previous studies have reported that intravitreal DEX implant treatment provides both functional and anatomic improvements in the treatment of diabetic, retinal vein occlusion, and uveitis-related macular edema in their study, including groups similar to our research 1,15 . Unlike these studies, retinal vein occlusions were evaluated in two different groups as branch and central in our study.…”
Section: Discussionsupporting
confidence: 77%
“…Two previous studies have reported that intravitreal DEX implant treatment provides both functional and anatomic improvements in the treatment of diabetic, retinal vein occlusion, and uveitis-related macular edema in their study, including groups similar to our research 1,15 . Unlike these studies, retinal vein occlusions were evaluated in two different groups as branch and central in our study.…”
Section: Discussionsupporting
confidence: 77%
“…As shown in previous studies, Ozurdex is also effective in persistent macular edema of variable etiologies such as retinal vein occlusion, uveitis or DME [11,12. ]The extended-release system Novadur® allows maintaining efficacy beyond the fourth month with a single injection.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have shown the efficacy of intravitreal steroids in DME. [12][13][14] In real life, intravitreal antiVEGF are more commonly used for diabetic macular edema and intraocular steroids are considered in a certain subset of patients with pseudophakia, recalcitrant edema, or systemic vascular comorbidities where anti VEGF agents are relatively contraindicated. We present here the results of intravitreal dexamethasone implant in treatment naïve DME.…”
Section: Introductionmentioning
confidence: 99%